Congress Grass: A Growing Menace for the environment - Amarjeet, Amarjeet; Singh, Attar; Punia, S. S.; Mehta, Satish (Indian Farming, 2015)
Parthenium is an obnoxious grass weed that can grow under all types of soil and weather conditions. It being a serious threat to our biodiversity and environment, the Parthenium weed needs to be controlled by any means and all steps taken to stop its spread further more.